1990
DOI: 10.1177/0951692890002004003
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Logical Issues in the Study of International Diffusion

Abstract: This discussion attempts to explore the concepts of diffusion and contagion as well as the nature of diffusion/contagion effects, and to suggest how they might operate. Using a series of logical analyses to continue the exercise of unpacking the concept of diffusion, which was initially presented in Most and Starr (1980), we are led to the conclusion that such processes are both less mystical and troublesome than they have often appeared in the literature. We argue that spatial diffusion processes may be disag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…5. The relevance of linkage-politics perspectives in the study of conflict diffusion is suggested in Most and Starr (1990) and Goertz (1994, p. 85). For applications of linkage-politics approaches to the international diffusion of ethnic conflict, see Lake and Rothchild (1998).…”
Section: Notesmentioning
confidence: 95%
See 1 more Smart Citation
“…5. The relevance of linkage-politics perspectives in the study of conflict diffusion is suggested in Most and Starr (1990) and Goertz (1994, p. 85). For applications of linkage-politics approaches to the international diffusion of ethnic conflict, see Lake and Rothchild (1998).…”
Section: Notesmentioning
confidence: 95%
“…The complexity of the concept of diffusion has been explicated in several books and articles, see, e.g., Rogers (1995), Mahajan and Peterson (1985), and Valente (1995). For an excellent analysis of the basic issues in the study of conflict diffusion, see Most and Starr (1990). 2.…”
Section: Notesmentioning
confidence: 98%
“…If party platforms are influenced by those of foreign incumbents, and their platforms eventually influence policy, 1 a path is created along which policies can diffuse transnationally. The policy diffusion literature emphasizes that actors in one national context may be influenced by actors in other states if links between them exist (e.g., Most and Starr 1990;Elkins and Simmons 2005;Simmons, Dobbin, and Garrett 2003;Hays 2007, 2008;Gilardi 1 The empirical evidence suggests that the average party-election platform feeds through to public-policy outputs (Kang and Powell 2010;also McDonald and Budge 2005;Budge et al ). 2010Plümper and Neumayer 2010;Ward and Cao 2012).…”
mentioning
confidence: 99%
“…The crucial point is, therefore, that spatial dependence or links between states must exist so that coup-proofing policies can diffuse, because these links facilitate learning and emulation (see also Most and Starr 1990;Elkins and Simmons 2005;Gilardi 2010;2012: 460f;Ward and Cao 2012). In the following, we elaborate on the possible explanatory mechanisms of coup-proofing diffusion based on learning and emulation (see also Braun and Gilardi 2006).…”
Section: Counterbalancing State Interdependence and Peer-group Effectsmentioning
confidence: 99%
“…For example, McGowan (2006: 15) were killed, seventeen (23.3 percent) were exiled, and twenty-one (28.8 percent) were arrested." It may thus seem plausible that rulers seek to exploit all possible sources of information for the implementation of coup-proofing policies, which makes it unlikely that this is based on domestic information only (Dolowitz and Marsh 2000;Most and Starr 1990;Elkins and Simmons 2005;Simmons et al 2006;Franzese and Hays 2008;Gilardi 2010Gilardi , 2012.…”
mentioning
confidence: 99%